3D printing of continuous carbon fibre reinforced powder-based epoxy composites. (August 2022) - Zhang, Haoqi; Zhang, Ka; Li, Aonan; Wan, Lei; Robert, Colin; Ó Brádaigh, Conchúr M.; Yang, Dongmin
Abstract: This paper presents an experimental study on 3D printing of continuous carbon fibre reinforced thermoset epoxy composites. Powder-based solid epoxy was electrostatically flocked on the 1K continuous carbon fibre tow and then melted to fabricate composite filaments. The produced filament was printed using a modified extrusion-based printer which melted and deposited the filament following designed printing paths, to form multilayer preforms with complex geometries. After vacuum bagging and oven curing, high tensile strength (1372.4 MPa) and modulus (98.2 GPa) were obtained in the fibre direction due to the good wettability of epoxy and the consequent high fibre volume fraction (56%). The tensile tests of open-hole composites were also conducted, in which the sample with designed stress-lines fibre paths was seen to improve the ultimate strength by 95% compared with the mechanically-drilled sample. Other case studies, such as a spanner and a lattice structure, further demonstrated the design freedom of produced filaments for complex geometries. Graphical abstract: Image 1 Highlights: A tapeline is built to produce 1K CF filaments via epoxy powder electrostatic deposition. Low porosity (0.3%) and high fibre fraction (56%) are achieved. High strength (1372.4 MPa) and modulus (98.2 GPa) are obtained in fibre direction. The manufacturing of composites structures with complex geometries is demonstrated. A 95% increase in strength is achieved for open-hole composites via stress-line paths.